Chronic Obstructive Pulmonary Disease: health status, activities of daily living, resistance training and exacerbation - Grüninger, Marina Sallum Barusso (Universidade Federal de São Carlos, 2018)
Background: Patients with COPD might present a physically inactive and a sedentary lifestyle, so they start a vicious circle of inactivity and deconditioning, which also causes a decrease in functional capacity. The onset of dyspnea and fatigue and disease progression leads to impairments in activities of daily living (ADL). The exercise training appears being one of the cornerstone in treatments of COPD. Despite of all evidences describing the benefits of resistance training, still unclear and understanding regarding the comparison between different intensities of resistance training. Furthermore, exacerbations are frequent in patients and repeated exacerbations have a profound influence on health status. These issues were the central aspect of this thesis. Objectives: to assess the limitation during ADL and whether London Chest Activity of Daily Living (LCADL) and Saint George’s Respiratory Questionnaire are able to reflect the real ADL limitation. To investigate ADL performance and dyspnea, exercise capacity and quality of life after 36 sessions of two different resistance training intensities. To summarize the existing evidence on the impact of exacerbation of COPD on health status. Methods: a cross-sectional study which assessed 48 COPD patients by SGRQ and LCADL and an ADL simulation was performed; a randomized parallel-group trial was performed, which one assessed ADL limitation, functional capacity, complaints and quality of life before and after 36 sessions of resistance training - n= 13: low-load/high repetition (LL/HR) and n=11: high-load/low-repetition (HL/LR) - combined with aerobic training. A systematic review was performed on PubMed from inception until September 2017. Results: LCADL% and SGRQ showed a moderate positive correlation with dyspnea and metabolic demand during ADL. The dyspnea in ADL3 and metabolic demand in ADL1 explained 33% of the variability in LCADL%. The dyspnea and metabolic demand in ADL3 explained 67% of the variability in SGRQ. Both intensities improved in the same magnitude dyspnea during ADL and LCADL, in exercise capacity, muscle strength. An interaction between intervention and time was observed in symptom domain of SGRQ with greater effect of time in LL/HR group. Based in 16 articles of which six studies assessed the direct effect of a single exacerbation on health status while 12 studies assessed the influence of exacerbation occurrence or exacerbation frequency on longitudinal changes over time. Conclusion: LCADL reflects 33% and SGRQ reflects 67% of the functional limitation during ADL simulation, such as dyspnea and the metabolic demand during ADL. There was a superior effect of LL/HR training in symptoms domain of SGRQ. Regarding the impact of exacerbations of COPD on health status, detrimental short- and/or long-term impact on symptoms related to activities of daily life and health-related quality of life was clearly revealed. The long-term impact of (repeated) exacerbations on exercise tolerance, muscle strength and physical activity levels is less studied and/or conflicting evidence is existing.
Keywords: COPD; Health status; Resistance training; Exacerbation; Activities of daily living; Atividades de vida diária; Treinamento resistido; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL